Postcard from Svante Arrhenius to Georg Bredig, December 1917 - Arrhenius, Svante (1917)
Svante Arrhenius (1859-1927) writes about World War I, politics, and updates on fellow scientists.
Keywords: Arrhenius, Svante, 1859-1927; Bredig, Georg, 1868-1944; World War (1914-1918); Franco-Prussian War (1870-1871); World politics; Chemists; Nobel Prize winners; Economics; Rindell, Arthur, 1852-1936